ANALYSIS OF MARUGOTO TEACHING MATERIALS IN JAPANESE LANGUAGE AND CULTURE: A1 ACTIVITIES FOR BEGINNERS - Rosalina Wahyu Riani; Umi Handayani; Teguh Santoso (Faculty of Economics, Law, and Humanities, 2022)
Marugoto Japanese Language and Culture teaching materials: Beginner A1 Activities can be used by Japanese language instructors and Japanese language learners as material resources to improve Japanese language skills. The purpose of this study is to describe the content components contained in the Marugoto Japanese Language and Culture teaching material: Beginner A1 Activity. This study uses a qualitative research method. This research is included in the type of content analysis used to examine teaching materials for Marugoto Japanese Language and Culture: Beginner A1 Activity. The data source is teaching material for Marugoto Japanese Language and Culture: Beginner A1 The activity. The results of this study indicate that the material and language components presented have been in accordance with the main objectives of language teaching. The advantage of this teaching material is that there are photographs and illustrative images that are colorful and interesting so that language learners are more interested in reading them. Then the textbook, also available in an online version (web). Meanwhile, the disadvantage is that the material in the teaching book is arranged randomly, making it difficult for teachers to deliver it. In addition, the learner has difficulty applying the material in it because the explanation books are arranged separately so that it is less optimal to use to learn independently.